COMPETENCIES RELATED TO INSTRUCTIONAL MANAGEMENT BASED ON THE COMPETENCY-BASED CURRICULUM AMONG TEACHERS IN EDUCATIONAL OPPORTUNITY EXPANSION SCHOOLS - Suwanno, Pitchaya; Jingwangsa, Piyada; Boonwanno, Jaraja; Tepsongkroh, Praman; Panjeang, Prapas; Chaiyakhet, Wachara; Tong-Ngern, Ratchanee (Journal of MCU Nakhondhat, 2025)
This research employed a mixed-methods design, integrating both qualitative and quantitative approaches. The objectives were: 1) To investigate the teaching competencies based on the competency-based curriculum among teachers in schools of Educational Sandbox, 2) To assess the professional development needs of teachers in educational opportunity expansion schools regarding competency-based teaching, and 3) To propose guidelines for developing teachers’ competencies in implementing the competency-based curriculum. The sample comprised 29 teachers and administrators from schools in the Educational Sandbox in Satun and Pattani Provinces, as well as 217 teachers from educational opportunity expansion schools in Songkhla Province, selected through purposive sampling. Research instruments included interview forms and questionnaires. Data were analyzed using means, standard deviations, and percentages, with results synthesized and presented descriptively. The findings revealed that: 1) The competencies of teachers in pilot schools consisted of six core competencies. The top three competencies most in need of development were curriculum management and instructional practice, learner development, and classroom management. 2) Regarding the development needs in learning management on Competency-based curriculum of teachers in opportunity expansion schools, the highest need was active learning pedagogy ( = 3.98), followed by authentic assessment ( = 3.91), and instructional design ( = 3.89). and 3) The proposed guidelines for teacher competency development in opportunity expansion schools emphasized at least four areas: 3.1) Competency-based curriculum knowledge, 3.2) Instructional design, 3.3) Assessment and evaluation, and 3.4) Innovation and technology for learning. The recommended development process should involve workshops combined with mentoring, consultation, and continuous follow-up.